Three-dimensional-guided perineal-based interstitial brachytherapy in cervical cancer: A systematic review of technique, local control and toxicities. Issue 2 (May 2017) - Mendez, Lucas C.; Weiss, Yonatan; D'Souza, David; Ravi, Ananth; Barbera, Lisa; Leung, Eric
Abstract: Objective: To evaluate local control and toxicities of perineal-based interstitial brachytherapy (P-ISBT) in cervical cancers treated with three-dimensional (3D) image-based planning through a systematic review. The secondary objective of this review is to summarize the implant and dosimetric techniques in 3D P-ISBT. Methods: Systematic review of the literature using the PRISMA guideline was conducted through a search of Medline, EMBASE and Cochrane databases. This search resulted in 19 relevant manuscripts. Selected studies evaluated the role of perineal ISBT in cervical tumours treated using 3D planning. Eleven of nineteen manuscripts contained sufficient information for LC and toxicity calculations. Data were extracted by at least two investigators. Results: A total of 672 cervical cancer patients were treated with P-ISBT and planned with 3D image-based planning. Clinical outcomes could be identified for 392 patients and 60% were staged IIIB or higher. Most patients received 45–50.4 Gy EBRT to the pelvis followed by a P-ISBT boost with a range of dose between 28 and 48 Gy EQD2Gy . Overall LC was 79% (310/392) with a median follow-up ranging from 14 to 55 months. Almost half of the patients (48%) had a median follow-up ≥35 months. Patients treated to a lower tumour EQD2Gy total dose had inferior LC. Procedure-related complications were rare (7 infections and 7 episodes of bleeding) and limited. Combined late gastro-intestinal, genitourinary and vaginal grade 3 and 4 toxicity was 12.1%. Conclusion: Promising LC rates were found in patients with cervical cancers treated with perineal ISBT with 3D image-based planning. In this systematic review, 60% had stage IIIB disease or higher and yet a LC rate of 79% was found. LC seemed to correlate with the dose delivered to the tumour, while toxicity rates were similar to other cervical cancer series using 3D image-based brachytherapy. Perineal ISBT with 3D planning seems to be an effective and safe treatment for large advanced cervical tumours and may be a reasonable alternative to the increasingly more standard and modern intracavitary/interstitial (IC/IS) approaches such as the ' Vienna ' applicator.